1998
DOI: 10.1002/(sici)1096-911x(199808)31:2<86::aid-mpo7>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Long-term gross motor performance following treatment for acute lymphoblastic leukemia

Abstract: Background The primary purpose of this descriptive study was to determine the long‐term effects of cancer treatment in childhood on musculoskeletal function and gross motor skills. Procedure. Musculoskeletal and gross motor function were assessed in a cohort of 36 survivors of acute lymphoblastic leukemia (ALL) seen in a pediatric tertiary care referral centre, compared to 36 age and gender matched comparison subjects. Basic gross motor skills were assessed using dimensions D: standing, and E: walking, running… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 20 publications
1
98
1
4
Order By: Relevance
“…Other studies that determined motor performance in the oncological aftercare revealed impairments in motor performance even years after cessation of treatment [4,10,37,38,41].…”
Section: Introductionmentioning
confidence: 98%
“…Other studies that determined motor performance in the oncological aftercare revealed impairments in motor performance even years after cessation of treatment [4,10,37,38,41].…”
Section: Introductionmentioning
confidence: 98%
“…Child survivors of ALL have lower levels of physical activity than their healthy referents, 8,[23][24][25] leading to worse cardiorespiratory fitness, 7,[26][27][28][29][30][31] physical function, 30 balance and coordination. 32 Identifying the effects of regular physical activity in adult and pediatric survivors of hematological cancer is thus of medical interest. Liu et al 33 recently performed a systematic review on exercise interventions conducted in hematological cancer patients, including studies published up to September 2007.…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in an increasing interest in the late effects of disease and treatment on physical, mental and social well-being of the survivors. Several elements of therapy for ALL may affect the function of the central and peripheral nervous system, and cognitive deficits (e.g., Anderson et al, 2000;Brown et al, 1992;Butler et al, 1994;Moleski, 2000;Ochs et al, 1991) as well as gross and fine motor impairments (Galea et al, 2004;HarilaSaari et al, 2001;Lehtinen et al, 2002;Reinders-Messelink et al, 1996;Vainionpaa, 1993;Wright et al, 1998) have been reported in survivors of childhood ALL. CNS-directed treatment is a standard component of therapy for ALL.…”
Section: Introductionmentioning
confidence: 99%